2005
DOI: 10.1061/(asce)0733-9429(2005)131:10(853)
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Surges in a Stormwater Storage Tunnel

Abstract: Below grade storage tunnels in stormwater systems are usually designed to operate in a free-surface flow regime. However, intense rain events may trigger flow regime transition to pressurized flow, which results in operational problems. To date, little guidance is available as to the considerations necessary to properly design a system undergoing flow regime transition. In this investigation, an experimental apparatus consisting of a 14.3 m long, 94 mm diameter acrylic pipe was used to observe the nature of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 9 publications
4
42
1
Order By: Relevance
“…The study was conducted on an experimental setup described by (Vasconcelos and Wright 2005). It consists of a 14.3 m long, 94 mm diameter acrylic pipeline, connected at the upstream end to an inflow box of lateral dimensions 0.25 m × 0.25 m, and at the downstream end with a surge riser of 0.19 m diameter.…”
Section: Mixed Flows: Rapid Pipe Fillingmentioning
confidence: 99%
“…The study was conducted on an experimental setup described by (Vasconcelos and Wright 2005). It consists of a 14.3 m long, 94 mm diameter acrylic pipeline, connected at the upstream end to an inflow box of lateral dimensions 0.25 m × 0.25 m, and at the downstream end with a surge riser of 0.19 m diameter.…”
Section: Mixed Flows: Rapid Pipe Fillingmentioning
confidence: 99%
“…intermittent air-water jets in the atmosphere) Song 1990, 1991), or even severely damage sewers (Hamam andMcCorquodale 1982, Zhou et al 2002a). Despite these potential drawbacks, the phenomenon has not been extensively explored; however, it has been established that intense and frequent pressure oscillations observed in experiments carried out in a variety of conditions are caused by the complex interaction between water flow and air pockets entrapped in pipes and manholes (Hamam and McCorquodale 1982, Zhou et al 2002b, Vasconcelos and Wright 2005. Moreover, various experiments have shown that the amount of entrapped air and the air pocket arrangement inside the water flow depend on the pipe pressurization pattern.…”
Section: Introductionmentioning
confidence: 99%
“…. What is more, air/water interactions may arise, particularly at the transition bore [5], and alter thoroughly the flow regime and its characteristics. On account of the range of applications affected by mixed flows, a good prediction of its features is an industrial necessity.…”
Section: Introductionmentioning
confidence: 99%